Interaction of non-indigenous endoparasites of the European eel Anguilla anguilla - Honka, Katrin Isabel (2024)
Biotic interaction is an essential feature of ecosystems, expressing their stable and dynamic structure. The present thesis is focusing on the interaction of different non-indigenous endoparasites of the European eel (Anguilla anguilla). One of them, Anguillicola crassus, is topic of research since decades, however very few is known about its interaction with other parasites. After this invasive parasite was found inside an acanthocephalan cyst (Pomphorhynchus spp.) – the second protagonist of the present thesis – it was indicated that there might be some beneficial interaction between both species. This work proves that hidden nematode larvae are still infectious to their final host, revealing previously unidentified but effective ways to complete their life cycle. It is already known that invasive parasites influence their new habitats to some extent. The here applied invasional meltdown hypothesis describes the beneficial influence of two non-indigenous species by accelerating the distribution of each other. Because this hypothesis was only used to describe interactions of free-living species, Pomphorhynchus spp. and A. crassus are the first parasites it is applied to. Furthermore, the co-evolutionary adaptation of host-parasite systems is considered in this thesis, as both parasites are native to different eel species. By analyzing plasma cortisol levels after inoculation, the co-evolutionary well adapted system of A. crassus with Japanese eels (A. japonica) revealed the lowest stress response, whereas the same eel species displayed the highest response to Pomphorhynchus spp. as a naïve parasite. Cortisol levels of the European eels ranged between those of the Japanese eel, but likewise with lower levels to the familiar parasite. The results underline the clear dependence of the cortisol response on mutual adaptation occurring in host-parasite systems, from high cortisol levels in naïve systems and low cortisol levels in adapted systems. When considering the invasional success of A. crassus, the focus of ...